2017
DOI: 10.3892/etm.2017.5479
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene protects against acute renal ischemia reperfusion injury and inhibits oxidative stress, inducible nitric oxide synthase expression and inflammation in rats via the Toll‑like receptor 4/nuclear factor‑κB signaling pathway

Abstract: Abstract. Previous studies have demonstrated that pterostilbene (Pter) prevents oxidative stress, suppresses cell growth and exhibits anti-fungal and anti-inflammatory effects. Pter is used to treat a number of clinical diseases, including Alzheimer's disease, various malignancies and hypercholesteremia. The aim of the present study was to investigate whether Pter protects against acute renal ischemia reperfusion injury (IRI) and inhibits oxidative stress, inducible nitric oxide synthase (iNOS) expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…A study also showed that PS inhibited the high fat-induced atherosclerosis inflammation via NF-κB signaling pathway [14]. Moreover, PS protected against acute renal ischemia reperfusion injury via the Toll-like receptor 4/NF-κB signaling pathway [15]. However, the effect of PS against DN has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…A study also showed that PS inhibited the high fat-induced atherosclerosis inflammation via NF-κB signaling pathway [14]. Moreover, PS protected against acute renal ischemia reperfusion injury via the Toll-like receptor 4/NF-κB signaling pathway [15]. However, the effect of PS against DN has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, the time period under obstruction is of critical importance. Antioxidant agents may be useful in order to protect kidney function and reserves until the extinction of the obstruction and after [23][24][25]. Planning of future studies including renal function tests may bring addition of antioxidants into first line treatment options in order to protect the functions of the hydronephrotic kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal ischemia-reperfusion (I/R) injury can be described as the damage occurring in ischemic renal cells after the reestablishment of the blood supply (Gao et al, 2018). Acute renal I/R injury is one of the pathological mechanisms underlying acute renal failure and is likely to occur following renal transplantation and septic shock (Gao et al, 2018). The pathophysiology of acute renal failure has been closely connected to tubular epithelial cell injury.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the use of Pte was reported to be beneficial in the treatment and prevention of myocardial (Yu et al, 2017), hindlimb (Cheng et al, 2016), and cerebral (Zhou et al, 2015) I/R injury. In addition, it was demonstrated to protect against acute renal ischemic injury by inhibiting oxidative stress and inflammation (Gao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation